PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN BELAJAR MAHASISWA DALAM PEMBELAJARAN SEJARAH MATERI POLITIK MASA REFORMASI 1998 - Flores Tanjung; Hafnita Sari Dewi Lubis; Arfan Diansyah (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2016)
The Study aims to increase students' understanding of history teachingin the subject matter "Future Political Reform (1998) in Indonesia. Subjects inthis research activity is the fifth semester students of history education, Faculty ofSocial, University of Medan, class A Regular school year 2016/2017. This type ofresearch is classroom action research. Collecting data using observation sheet and test. Collecting data using observation sheet and test. Data were analyzed using descriptive analysis. The study consisted of two cycles with each cycle of four stages.The stages of the implementation is the planning, implementation, observatiol and reflection. The results of the study that (1) PBL Learning model can improve students’ learning comprehension up to 54.09% and (2) ) PBL Learning model can improve students’ achievement of the lesson improved up to 56.77%